2010
DOI: 10.1002/ana.21958
|View full text |Cite
|
Sign up to set email alerts
|

Long‐interval T2‐weighted subtraction magnetic resonance imaging: A powerful new outcome measure in multiple sclerosis trials

Abstract: Compared with monthly Gd-T1w imaging, long-interval T2w-Sub MRI exhibited increased power to assess treatment efficacy, and could greatly increase the cost-effectiveness of phase 2 MS trials by limiting the number of patients, contrast injections, and MRI scans needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Long interval T2 weighted sequences can be processed with automated subtraction, which has been used in a multicentre trial to provide greater power for assessing treatment efficacy than is possible with monthly contrast enhanced T1 weighted imaging. 90,91 Application of automated subtraction in treatment trials or for treat ment monitoring can improve cost effectiveness and lower the risk of adverse effects associated with repeated contrast administration. Recent data have shown that automated identification of new and/or enlarged T2 lesions is robust, accurate and sensitive, thus supporting its use for evaluating treatment efficacy in clinical trials.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…Long interval T2 weighted sequences can be processed with automated subtraction, which has been used in a multicentre trial to provide greater power for assessing treatment efficacy than is possible with monthly contrast enhanced T1 weighted imaging. 90,91 Application of automated subtraction in treatment trials or for treat ment monitoring can improve cost effectiveness and lower the risk of adverse effects associated with repeated contrast administration. Recent data have shown that automated identification of new and/or enlarged T2 lesions is robust, accurate and sensitive, thus supporting its use for evaluating treatment efficacy in clinical trials.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…The resulting lesion masks were visually checked to ensure lesions were not identified as the result of changes in partial volume effect or atrophy between scans. These segmented lesions we refer to as ΔMTR lesions and can be considered analogous to T2 or T1 lesions segmented using an image subtraction methodology (Moraal et al, 2010).…”
Section: δMtr Lesion Segmentationmentioning
confidence: 99%
“…sMRI is capable of detecting even small white matter changes in longitudinal evaluations with high intra- and inter-observer agreement12 14 and a sensitivity significantly higher than that provided by serial total T2LV change 21. In a recent re-analysis of a placebo controlled clinical trial, monthly CEL counts were compared with 9 month interval change measures using sMRI between the first and last month MRI examinations: sMRI showed markedly increased power to detect a treatment effect, with the additional advantage of being safer as it did not require gadolinium administration 14…”
Section: Discussionmentioning
confidence: 99%
“…While subtraction MRI (sMRI) metrics have demonstrated sensitivity to subtle changes in lesion burden and increased power in clinical trials,12 14 their relationship with other clinical and neuroimaging measures of MS disease activity and progression has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%